Whip use in trotting racing–effects on speed change and finishing position - Sandberg, Agneta; Melani, Mirielle; Flöhr, Adam; Yngvesson, Jenny (Frontiers in Animal Science, 2025)
The whip is used in several equine sports. This is intensely debated from a horse welfare perspective and putting the equine sports’ social license to operate at risk. Trotting racing is one of the sports where whip use is allowed. The whip is used for making the horse accelerate (encouragement) and correction. The aims of the study were to investigate if finishing position among top three horses is affected by whip use, the effect of whip strikes on changes in speed at the end of trotting races and if whip strikes potentially comply with the training principle of negative reinforcement. Race videos were analyzed retrospectively, whip strikes were registered and compared with changes in speed, which could be read out of position data from the same races. The top three horses (n=48) in 16 races were studied. The number of strikes per horse ranged from 0 to 16, with a mean of 5.6. There was no difference in number of strikes received between horses in finishing positions 1-3, and whip strikes were most often followed by deceleration. Whip strikes followed by deceleration may be an example of negative reinforcement. Whip strikes to encourage trotting horses to run faster at the end of a race should be avoided from a horse welfare perspective. The safety aspects of whip use in trotting racing need to be investigated further.